Chronic Primary or Secondary Noninflammatory Musculoskeletal Pain and Disrupted Sexual Function and Relationships: A Systematic Review. Issue 6 (25th March 2022) - Briggs, Andrew M.; Slater, Helen; Van Doornum, Sharon; Pearson, Lauren; Tassone, Eliza C.; Romero, Lorena; Chua, Jason; Ackerman, Ilana N.
Abstract : Objective: Evidence points to the impact of chronic musculoskeletal pain conditions on sexual function, yet there is little systematic appraisal and synthesis of evidence examining these associations across noninflammatory conditions. We aimed to systematically review evidence surrounding the association between chronic primary and chronic secondary musculoskeletal pain with intimate relationships and sexual function. Methods: Four electronic databases were searched from January 1, 1990 to September 5, 2019 for cross‐sectional or prospective epidemiologic and qualitative studies among cohorts with chronic primary or secondary noninflammatory musculoskeletal pain, defined by International Classification of Diseases, Eleventh Revision classification criteria. Results: Fifty‐one eligible studies were included (46 quantitative, 3 qualitative, 2 mixed‐methods designs). Sample sizes ranged from 13 to 12, 377 and mean age from 32.6 to 69.2 years. Cross‐sectional controlled cohort studies consistently reported poorer sexual function outcomes among cohorts with pain relative to comparison groups. Of 15 studies reporting outcomes for the Female Sexual Function Index, 14 demonstrated mean scores of ≤26.55 for the pain group, indicating sexual dysfunction. In 4 studies reporting the International Index of Erectile Function, the pain cohorts demonstrated consistently lower mean subscale scores and the erectile function subscale scores were ≤25.0, indicating erectile dysfunction. Three key themes emerged from a meta‐synthesis of qualitative studies: impaired sexual function; compromised intimate relationships; and impacts of pain on sexual identity, body image, and self‐worth. Conclusion: Sexual dysfunction and negative impacts on intimate relationships are highly prevalent among people with chronic noninflammatory musculoskeletal pain. Consideration of these associations is relevant to the delivery of holistic, person‐centered musculoskeletal pain care.